Assessment and economic analysis of solid and hazardous waste management in Barangay UP Campus - Hernandez, Pauline Mae E.; Seranilla, Justin Jesse L.
The study alms to assess the status of the current solid and hazardous waste management in Brgy. UP Campus, Quezon City, and also to analyze the economic aspects of the program. The assessment involves quantifying the waste generation rate, evaluation of the resident's practices as observed on actual collections, and conduction of waste analysis and characterization study to determine the waste composition and assess the segregation practice of the people. In addition to that, survey data regarding residents' disposal practices of hazardous waste was analyzed and subjected to statistical analysis. To further evaluate and improve the efficiency of the system, an economic analysis involving a comparison of benefit-cost ratio of several hypothetical scenarios was conducted. Results showed that the overall waste generation rate for 2015 is 0.319 kg/capita-day, higher than the generation rate of 0.180 kg/capita-day in 2012 and 0.256 kg/capita-day in 2013. A significant amount of biodegradable waste is stilI present in the non-biodegradable collection, indicating the non-compliance to segregation of some residents. The disposal practice for hazardous waste, on the other hand, is most commonly by disposing with other solid waste. To address the growing rate of waste generation and to add benefits to the system, it was determined best to have a recycling facility which will collect the recyclable materials from the solid waste collections. Lastly, a set of recommendations which includes pointers for improvement is presented and explained to address the current problems in the solid waste management program and to provide a more efficient program.